Proposal of a new scoring formula for the DLQI in psoriasis. (2nd November 2018) - Rencz, F.; Gulácsi, L.; Péntek, M.; Poór, A.K.; Sárdy, M.; Holló, P.; Szegedi, A.; Remenyik, É.; Brodszky, V.
Summary: Psoriasis is a common skin disease affecting approximately 2% of the population. Psoriasis can have a negative impact on patients' everyday activities and wellbeing. Dermatology Life Quality Index (DLQI) is a widely used measure to assess quality of life in patients with psoriasis. It consists of 10 questions covering symptoms and feelings, daily activities, leisure, work and school, personal relationships and treatment. Each question is scored as follows: 'not at all'=0, 'a little'=1, 'a lot'=2 and 'very much'=3. However, certain questions of the DLQI such as sports, sexual difficulties and working/studying are not relevant to every patient. As 'not relevant' responses are scored as if the item of the questionnaire had no impact on patients' life at all (=0), they may artificially improve patients' quality of life scores. For these patients, despite having severe psoriasis, it is more difficult to fulfil the DLQI threshold required by clinical guidelines to become candidates for stronger, systemic treatments such as biologics. This study, from Hungary, involved 242 patients with psoriasis. The authors developed a new scoring for the DLQI questionnaire, namely the DLQI‐R that corrects for the bias in the 'not relevant' response option, and proved its validity (i.e. that it works). The DLQI‐R scoring formula eliminates the items marked as 'not relevant' while increasing the weight of the relevant items in the total score of the questionnaire. It primarily strives to provide fair access to systemic treatments for psoriasis patients who cannot comply with the DLQI criteria in treatment guidelines because certain items of the questionnaire are simply not relevant to them. Abstract : Linked Article: Rencz et al. Br J Dermatol 2018; 179 :1102–1108